Ceramic article and method of making the same
Patent Information
- Application Number
- JP2024208771
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-12-29
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure 2025037983000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure generally relates to a composite material comprising a plurality of first alumina particles forming a continuous matrix, and a matrix. and a plurality of second alumina particles dispersed within the matrix. The first and second pluralities of alumina particles have different dye penetration test values. The present invention relates to a catalyst that incorporates catalytically active material on the surface of a laminated article. Summary of the Invention [Problem to be solved by the invention]
[0002] The catalyst is generally supported on a support, typically a ceramic article made from a ceramic material. , by impregnation with a catalytically active material, such as a metal. However, catalysts with too high a weight ratio of catalytically active material to support may be undesirable. For example, even if a catalyst has a long life due to a high loading of catalytically active material, the reaction When used in a reactor where low catalyst loading per unit volume of the reactor is desired, The catalyst can become very expensive and economically unfeasible. The structure of the support allows for adjustment of the loading of active catalytic material in the catalyst body. There is a need in the art for novel biocompatible carriers.
[0003] The present disclosure relates to ceramic articles comprising hard formations of alumina particles. , a plurality of first alumina particles and a plurality of second alumina particles. Both plurality of particles are , randomly distributed throughout the hard formation. The second alumina particles are 5 atomic percent The first alumina particles have a ZnI2 dye penetration test value of 0.1 to 0.25% and the second alumina particles have a ZnI2 dye penetration test value of 0.1 to 0.25%. Has a ZnI2 dye penetration test value that is at least twice the nI2 dye penetration test value. Hard Formulation Each of the plurality of particles occupies a portion of the total cross-sectional area, and the second alumina particles The cross-sectional area of each is 5% to 50% of the total cross-sectional area.
[0004] In some aspects, embodiments of the ceramic article include a continuous matrix (i.e., a first The ZnI2 dye penetration test value of the dispersed phase (i.e., the second alumina powder) is lower than that of the In one embodiment, the first alumina particles have a ZnI2 dye penetration test value of 1.0001. A ceramic having a dye penetration test value of at least 2:1 to a dye penetration test value of a second alumina. In one embodiment, the dye penetration test value is measured by scanning electron microscopy. electron microscopy, SEM, and energy dispersive X-ray spectroscopy Ceramic objects obtained by a method including one or more of the following: One embodiment relates to a ceramic material having a penetration test value determined by a ZnI2 dye penetration test. One embodiment relates to a composite article comprising a plurality of first alumina particles forming a continuous matrix. Regarding ceramic articles in which the particles have a ZnI2 dye penetrant test value of 10 atomic percent or more In one embodiment, the plurality of second alumina particles forming the dispersed phase is 5 atomic percent. For ceramic articles having the following ZnI2 dye penetration test values:
[0005] In some aspects, embodiments of the ceramic article have a thickness of about 0.2 cm 3 / g ~ approx. 0.7cm 3 / g. One embodiment has a total pore volume of about 0.3 cm 3 / g~approx. 0.6cm 3 One embodiment relates to a ceramic article having a total fineness of 1 / g. Pore volume is approximately 0.35 cm 3 / g ~ approx. 0.5cm 3 / g. The embodiment has a total surface area of about 0.4 m 2 / g ~ approx. 3m 2 / g for ceramic articles One embodiment has a total surface area of about 0.4 m 2 / g ~ approx. 1.5m 2 / g of ceramic article One embodiment relates to a surface area of about 0.5 m 2 / g~approx.0.85m 2 / g Sera Regarding mixed items.
[0006] The present disclosure also provides methods for preparing metallurgical articles, including metals, deposited on the ceramic articles described herein. One embodiment relates to a catalyst body in which the metal is silver. One embodiment relates to a catalyst body in which the metal is silver. The present invention relates to a catalytic body comprising silver deposited on a ceramic article, the ceramic article being a continuous alumina matrix. and dispersed alumina as multiple discrete domains within a continuous alumina matrix. and the article is 0.3 cm 3 / g~0.6cm 3 / g total pore volume and 0.5 m 2 / g~0.85m 2 / g, and the continuous alumina matrix has a total surface area of 10 % or more of ZnI2 dye penetration test value, and the dispersed alumina phase has 5 atomic percent or less of Z The ceramic article has a dye penetrant test value of nI2, and the dispersed alumina phase comprises 5% to 50% of the cross-sectional area of the ceramic article. Covers %.
[0007] In one embodiment, the first plurality of alumina particles and the second plurality of alumina particles are α-alumina. The present invention relates to a method for making a ceramic article comprising: The present invention relates to a method for making a ceramic article, wherein the alumina particles comprise fused alumina. One embodiment includes a method for making a ceramic article, wherein the second plurality of alumina particles comprises platelet-like alumina. One embodiment relates to a method for making a ceramic article comprising a bonding material. For the method of claim 1, the binding material is magnesium silicate. [Brief description of the drawings]
[0008] The foregoing summary, as well as the following detailed description of the invention, is better read in conjunction with the accompanying drawings. It will be well understood. [Figure 1] FIG. 1 shows the surface area and water absorption of a ceramic article as a function of the amount of dispersed phase. [Figure 2A] FIG. 2A shows the microstructure of an article of the present invention at magnifications of 100×, 250×, and 500×, respectively. [Figure 2B] FIG. 2B shows the microstructure of an article of the present invention at magnifications of 100×, 250×, and 500×, respectively. [Figure 2C] FIG. 2C shows the microstructure of an article of the present invention at magnifications of 100×, 250×, and 500×, respectively. [Figure 3A] FIG. 3A shows an SEM image of an article of the invention that was mounted in epoxy, cross-sectioned, and polished to a 1 μm finish. [Figure 3B] FIG. 3B shows an SEM image of an article of the invention that was mounted in epoxy, cross-sectioned, and polished to a 1 μm finish. [Figure 4A] FIG. 4A shows energy dispersive X-ray spectroscopy (EDS) data processing for ZnI dye penetration testing. [Figure 4B] FIG. 4B shows the energy dispersive X-ray spectroscopy (EDS) data processing for the ZnI dye penetration test. [Figure 5A] FIG. 5A shows EDS data for another embodiment of the present invention. [Figure 5B] FIG. 5B shows EDS data for another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present disclosure generally relates to a method for producing, for example, ethylene oxide, in a variety of applications, including catalyst support applications. As a catalyst support for the catalyst used in the direct oxidation of ethylene to produce ethylene. The ceramic articles described herein relate to ceramic articles that can be used in at least one The present disclosure also provides a method for producing a composite material comprising the steps of: The present invention relates to a method of making an article from first alumina particles and second alumina particles.
[0010] While not wishing to be bound by any particular theory, the This solves the problem of how to adjust the amount of active catalytic material loaded on the support so that It is possible to provide a ceramic article for making a catalyst support that can be used to For example, lower catalyst loading on a volumetric basis in the reactor may be desirable to be more economically competitive. As described herein, it is believed that silver-containing The addition of high density (i.e., low porosity) regions throughout the soaked catalyst allows the catalyst to be more dense than the low porosity regions. The results simulated a higher work rate than would be possible with an otherwise identical catalyst that does not contain This allows the reactor to be cooled while maintaining the reactor production rate. In some embodiments, such adjustments allow for a reduction in the amount of silver in the catalyst system, e.g., It is possible to simulate high work rates in ethylene oxidation (EO) catalyst systems. By introducing large high density / low porosity regions into the support, the active catalytic material can be infiltrated. However, there will be areas in the carrier where it is not possible to In the matrix regions surrounding the low porosity regions, the ratio of water absorption to surface area remains conserved. and maintains the expected concentration and particle size of the active catalytic material in the matrix region. By maintaining the ratio of water absorption to surface area in the triplex region, the active catalyst on the support The total loading of the catalyst material is reduced, but the support is made without large high density / low porosity regions. In comparison, the initial catalyst performance is expected to be maintained. In this case, using less active catalytic material, such as silver, provides an economic advantage. As a result, greater amounts of active catalyst material do not provide any benefit over the life of the catalyst. The shrinkage of the alumina used in the support is due to the shrinkage of one or more alumina particles during the heat treatment of the support during manufacture. It is desirable that the structure be suitably adapted to avoid cracks around the periphery of the element. Porosity, also introduced by cracks, changes the ratio of water absorption to surface area of the matrix phase. This may result in the degradation of the device, an effect that reduces some of the advantages introduced by the present invention. may have.
[0011] One embodiment relates to a ceramic article, the article comprising a plurality of first alumina particles. The second alumina includes a matrix and a dispersed phase including a plurality of second alumina particles. The particles are distributed within a continuous matrix and can be described as a number of discrete domains. The phase has a ZnI2 dye penetrant test value different from the continuous matrix and is In an aspect, the dispersed phase occupies from about 8% to about 40% of the cross-sectional area of the ceramic article.
[0012] As used herein, the term "ratio" refers to the ratio of a particular characteristic (e.g., weight, grain size, etc.) to a specific characteristic (e.g., grain size, grain size, etc.). a first quantity of a characteristic (e.g., diameter, atomic percent, surface area, fraction of cross-sectional area, etc.) and a second quantity of the same characteristic In the following, we provide several illustrative examples. In the first example, The first alumina has a total mass of 100 grams and is made of a first alumina and a second alumina. Two alumina powders, one of which was 95 grams and the second was 5 grams. In the final mixture, the ratio of the first alumina to the second alumina is 95:5. In this case, the ratio can be written as 19:1. The amount of each alumina is expressed as a percentage of the total alumina. When expressed as a percentage by weight, the percentage of the first alumina is 95 percent by weight and the percentage of the second alumina is 95 percent by weight. In the second example, the percentage of alumina is 5 weight percent. 50 Particle size is 1 0 microns, and the d of the second alumina 50 If the particle size is 150 microns, the ratio is The ratio is 10:150, which can be simplified to 1:15. Mina's d 50 The particle size of the first alumina is d 50 The particle size must be 15 times larger than the particle size. In the example of 3, the surface area of the first alumina is 5 m 2 / g, and the surface area of the second alumina is 0 .5m 2 / g, the ratio is 5:0.5, which can be written as 10:1 This ratio is based on the fact that the surface area of the first alumina is 10 times greater than the surface area of the second alumina. In the fourth example, the total cross-sectional area of the article is 10 cm 2 and the total cross-sectional area of the article is 8 cm 2 The first powder occupies 2 cm 2If the second powder occupies only the first The ratio of the cross-sectional areas occupied by the first and second powders, respectively, is 8:2, which is written as 4:1. This ratio can be calculated by dividing the cross-sectional area occupied by the first powder by the cross-sectional area occupied by the second powder. The first powder must be 4 times larger than the cross-sectional area it occupies. The first powder occupies 80 percent of the cross-sectional area and the second powder occupies 20 percent of the total cross-sectional area. In the fifth example, the total cross-sectional area of the article is 10 cm 2 and the total cross-sectional area is 5 cm 2 First to occupy Powder and 5cm 2 When the first and second powders are composed of only the second powder occupying the first and second powders, The ratio of the cross-sectional area they occupy is 5:5, which can be written as 1:1. The first powder occupies 50 percent of the total cross-sectional area, and the second powder occupies 50 percent of the total cross-sectional area. In the sixth example, the total cross-sectional area of the article is 20 cm 2 and the total cross-sectional area is 19 .0cm 2 The first powder occupies 1.0 cm 2 In the case where the second powder occupies only In this case, the ratio of the cross-sectional areas occupied by the first and second powders, respectively, is 19:1. The first powder occupies 95 percent of the total surface area and the second powder occupies 5 percent of the total surface area. Therefore, the cross-sectional area of the first alumina particle and the cross-sectional area of the second alumina particle are In an embodiment in which the ratio of the cross-sectional area of the first aluminum alloy to the cross-sectional area of the second aluminum alloy is 1.0:1.0 to 19.0:1.0, The cross-sectional area of the first alumina is 50% to 95% of the total cross-sectional area, and the cross-sectional area of the second alumina is 100% of the total cross-sectional area. It is 50% to 5%.
[0013] One embodiment of the invention described herein includes a plurality of first alumina particles and a plurality of second alumina particles. A ceramic article comprising a hard matrix of alumina particles comprising alumina particles of both The plurality of particles are randomly distributed throughout the hard formation. The second alumina particles are 5-atom. The first alumina particles have a ZnI2 dye penetration test value of less than or equal to 1.5%. The ZnI2 dye penetration test value is at least twice the ZnI2 dye penetration test value of the Mina particles. Each of the plurality of particles occupies a portion of the total cross-sectional area of the hard formation. The laminated article is preferably made to cover about 8% to about 40% of the cross-sectional area thereof, more preferably 10% to 30% of the entire cross-sectional area thereof. A catalytically active metal is dispersed on the first and second alumina particles.
[0014] Another embodiment of the invention described herein is a method for producing alumina particles and a catalyst in contact with the particles. A process for the manufacture of an article comprising a hard formation with a catalytically active metal. The process The steps include: 50 Having a particle size A plurality of first alpha alumina particles are provided. The first alpha alumina particles are provided having a known weight, and the second alpha alumina particles are provided having a known weight. The first alpha alumina particles are provided having a known weight. The second alpha alumina particles are provided having a known weight. alumina particles, the second alumina particles being selected from the group consisting of alpha alumina particles, The nanoparticles are about 5 to 400 microns in diameter. 50 The first alumina particles have a particle size of d 50 grain Diameter and d of the second alumina particle 50 The ratio of the particle size to the grain size is 1:4 to 1:40. The ratio of the weight of the first alumina to the weight of the second alumina is 1:1 to 19:1. The particles are mixed together, thereby forming a mixture in which the particles are randomly distributed throughout the mixture. The mixture is formed into a plurality of malleable articles. The malleable articles are heated to a sintering temperature of the alumina particles. and heating each of the malleable articles to form a hard formation of alumina grains, each of the plurality of grains being The particles in the alloy are randomly distributed throughout the hard formation. A catalytically active metal is deposited on the mina particles.
[0015] As used herein, a continuous matrix refers to a matrix that is distributed throughout the article in any direction. , morphological characteristics that remain relatively unchanged over distances at least greater than the longest particle in the dispersed phase When viewed in cross section, the continuous matrix is a portion of a ceramic article having a dispersed Discrete regions of a dispersed phase that appear as individual, separate particles that rarely come into contact with other particles of the phase. The definition of a continuous matrix is that in a particular formulation, This applies even though the material may contain holes that may introduce gaps in the material. See FIG. 2C. Region 212 is then part of a continuous matrix, and region 206 is a discrete region of the dispersed phase. and region 218 is the pore region. This definition is based on the fact that, at a certain magnification, At high magnifications, areas of the matrix may not appear continuous due to the field of view (magnification). The rate of application is not negated by the inappropriate selection of visual inspection techniques. stomach.
[0016] As used herein, a dispersed phase is generally an island that encompasses a continuous matrix. This definition of the dispersed phase means that some dispersed regions are isolated from other dispersed regions. However, the dispersed phase may be adjacent to, in contact with, or sintered into the dispersed region of the 3A, which shows adjacent discrete regions 302 and 304 of the same. In contrast, as shown in FIG. In particular, region 501 is part of a continuous matrix, and region 502 is a discrete region in the dispersed phase. do.
[0017] The coverage of the dispersed phase on the cross section can be measured at a magnification of 100 to 250 times, but any Other suitable magnifications may be used. In some embodiments, the cross-sectional area is about 0.6 m and a first dimension of about 0.45 mm to about 1 mm. In some embodiments, the first dimension may be a length and the second dimension may be a width. In some embodiments, in a cross-section of the ceramic article, a majority of the plurality of discrete regions are about 10 Without being bound by any particular theory, the longest dimension appears to be between about 150 μm and about 200 μm. Although it is not our intention to limit the scope of the invention, the size may be any size of a discrete region, such as the Feret diameter ( For example, Henk G. Merkus, Particle Size Measurement ents:Fundamentals,Practice,Quality;1 Jan uary 2009;Springer,p.15).
[0018] The penetration test values are determined using the ZnI2 solution penetration test described below. Dispersed Phase The ZnI2 dye penetration test value of the matrix is lower than that of the continuous matrix. Generally, ZnI2 dye penetration test values are determined by using a ZnI2-containing solution to convert a ceramic article into Zn. It is obtained by subjecting the article to an I2 dye penetration test, e.g. by immersing the article in a solution. Thus, when a ceramic article is contacted with a ZnI2 solution, the solution is absorbed into the ceramic article. Once absorbed into the ceramic article, the solution is capable of detecting various chemicals by a variety of analytical methods. These include compounds that can be identified as absorbed into products.
[0019] Generally, the ZnI2 used to determine the penetration test value is dissolved in a suitable solvent, e.g. One or more samples of the ceramic article are introduced into the resulting ZnI2 solution. Optionally, the solution containing the ceramic material can be subjected to a vacuum, which causes the ceramic This ensures better penetration of the solution into the mixed article. After this, drying is used to remove the solvent, leaving the ZnI2 embedded in the ceramic article. Dried samples are mounted by fixing the sample in a polymer or resin material. The samples may be polished, cut, or both, as necessary, to provide a smooth surface for the ceramic article. A ceramic article sample is carbon coated and then scanned with a scanning electron microscope. The matrix is analyzed by scanning electron microscopy (SEM) and / or energy dispersive X-ray spectroscopy. The amount of permeation test material in the mixed and dispersed phases was calculated to determine the permeation rate of each region. A test value can be calculated.
[0020] In some embodiments, the difference in the penetration test values is at least 5%. The difference in the penetration test value is at least 5.1%, at least 5.2%, at least 5.3%, or a little at least 5.4%, at least 5.5%, at least 5.6%, at least 5.7%, at least 5.8%, at least 5.9%, at least 6%, at least 6.1%, at least at least 6.2%, at least 6.3%, at least 6.4%, at least 6.5%, at least 6.6%, at least 6.7%, at least 6.8%, at least 6.9%, At least 7%, at least 7.1%, at least 7.2%, at least 7.3%, at least 7.4%, at least 7.5%, at least 7.6%, at least 7.7%, at least 7.8%, at least 7.9%, at least 8%, at least 8.1%, at least 8. 2%, at least 8.3%, at least 8.4%, at least 8.5%, at least 8. 6%, at least 8.7%, at least 8.8%, at least 8.9%, at least 9% , at least 9.1%, at least 9.2%, at least 9.3%, at least 9.4% , at least 9.5%, at least 9.6%, at least 9.7%, at least 9.8% , at least 9.9%, or at least 10%.
[0021] In some embodiments, the ZnI2 dye penetration test value of the first alumina is greater than the ZnI2 dye penetration test value of the second alumina. The Znh dye penetration value is at least three times greater.
[0022] In some embodiments, the ZnI2 dye penetration test value of the first alumina is greater than the ZnI2 dye penetration test value of the second alumina. is at least 4 times larger than the ZnI2 dye penetration value.
[0023] In some embodiments, the dye penetration of the continuous matrix relative to the dye penetration test value of the dispersed phase In another embodiment, the ratio of the dye penetration test values of the dispersed phase is at least 2.0. The ratio of the penetration test value of the continuous matrix to that of the continuous matrix is at least 2.1, at least 2.2, or At least 2.3, at least 2.4, at least 2.5, at least 2.6, at least 2.7, at least 2.8, at least 2.9, at least 3, at least 3.1, at least At least 3.2, at least 3.3, at least 3.4, at least 3.5, at least 3 .6, at least 3.7, at least 3.8, at least 3.9, at least 4, at least Also 4.1, at least 4.2, at least 4.3, at least 4.4, at least 4. 5, at least 4.6, at least 4.7, at least 4.8, at least 4.9, or At least 5.
[0024] In some embodiments, the continuous matrix has a ZnI2 penetration test value of greater than 10%. In other embodiments, the continuous matrix is at least 10%, at least 11%, At least 12%, at least 13%, at least 14%, at least 15%, at least At least 16%, at least 17%, at least 18%, at least 19%, at least 20% , at least 21%, at least 22%, at least 23%, at least 24%, less At least 25%, at least 26%, at least 27%, at least 28%, at least 29% %, at least 30%, at least 31%, at least 32%, at least 33%, at least at least 34%, at least 35%, at least 36%, at least 37%, at least 3 8%, at least 39%, at least 40%, at least 41%, at least 42%, at least at least 43%, at least 44%, at least 45%, at least 46%, at least 47%, at least 48%, at least 49%, or at least 50% ZnI2 penetration test It has experimental value.
[0025] In some embodiments, the dispersed phase has a ZnI2 dye penetration test value of 5% or less. In embodiments, the dispersed phase is less than 1%, less than 1.1%, less than 1.2%, less than 1.3%, less than 1. Less than 4%, Less than 1.5%, Less than 1.6%, Less than 1.7%, Less than 1.8%, Less than 1.9%, Less than 2%, Less than 2.1%, Less than 2.2%, Less than 2.3%, Less than 2.4%, Less than 2.5%, Less than 2.6%, Less than 2.7%, Less than 2.8%, Less than 2.9%, Less than 3%, Less than 3.1%, Less than 3.2%, Less than 3.3%, Less than 3.4%, Less than 3.5%, Less than 3.6%, Less than 3.7% Less than 3.8%, Less than 3.9%, Less than 4%, Less than 4.1%, Less than 4.2%, Less than 4.3% less than 4.4%, less than 4.5%, less than 4.6%, less than 4.7%, less than 4.8%, or Has a ZnI2 dye penetration test value of less than .9%.
[0026] In some embodiments, the ceramic article is about 0.2 cm 3 / g ~ approx. 0.7cm 3 / g In some embodiments, the ceramic article has a total pore volume of about 0.3 cm 3 / g~ Approx. 0.6cm 3 In some embodiments, the ceramic article has a total pore volume of about 0.35cm 3 / g ~ approx. 0.5cm 3 The total pore volume of the carrier is 1 / g. The pore size and pore size distribution of the mercury intrusion porosity were determined by the conventional mercury intrusion porosity method, which involves forcing liquid mercury into the pores of the support. This can be measured by a symmetry device. To force the mercury into smaller pores, Large pressures are required, and the measured pressure increment corresponds to the volume increment of the infiltrated pores. The pore size distribution and pore volume of alumina are given by M icromeritics Model 9520 Autopore IV (130° mercury contact angle of 0.480 N / m, mercury with a surface tension of 0.480 N / m, and mercury compression applied. Starting at 689 Pa, then 4.1×10 7 Increase to Pa It can be measured by mercury intrusion porosimetry. A minimum of 100 data points is appropriate. As used herein, the median pore size is the point at which 50% of the total pore volume is greater than that point. The pore size distribution corresponds to a point in the pore size distribution found in pores smaller (or larger) than the "diameter" is understood to mean the diameter
[0027] In another embodiment, the ceramic article is 0.20 cm 3 / g, approx. 0.21cm 3 / g , about 0.22cm 3 / g, approx. 0.23cm 3 / g, approx. 0.24cm 3 / g, approx. 0.25c m 3 / g, approx. 0.26cm 3 / g, approx. 0.27cm 3 / g, approx. 0.28cm 3 / g, about 0 .29cm 3 / g, 0.30cm 3 / g, approx. 0.31cm 3 / g, approx. 0.32cm 3 / g , about 0.33cm 3 / g, approx. 0.34cm 3 / g, approx. 0.35cm 3 / g, approx. 0.36c m 3 / g, approx. 0.37cm 3 / g, approx. 0.38cm 3 / g, approx. 0.39cm 3 / g, 0. 40cm 3 / g, approx. 0.41cm 3 / g, approx. 0.42cm 3 / g, approx. 0.43cm 3 / g , about 0.44cm 3 / g, approx. 0.45cm 3 / g, approx. 0.46cm 3 / g, approx. 0.47c m 3 / g, approx. 0.48cm 3 / g, approx. 0.49cm 3 / g, 0.50cm 3 / g, about 0. 51cm 3 / g, approx. 0.52cm 3 / g, approx. 0.53cm 3 / g, approx. 0.54cm 3 / g , approx. 0.55cm 3 / g, approx. 0.56cm 3 / g, approx. 0.57cm 3 / g, approx. 0.58c m 3 / g, approx. 0.59cm 3 / g, approx. 0.60cm 3 / g, approx. 0.61cm 3 / g, about 0 .62cm 3 / g, approx. 0.63cm 3 / g, approx. 0.64cm 3 / g, approx. 0.65cm 3 / g, approx. 0.66cm 3 / g, approx. 0.67cm 3 / g, approx. 0.68cm 3 / g, approx. 0.69 cm 3 / g, or about 0.70 cm 3 / g pore volume.
[0028] In some embodiments, the ceramic article is about 0.4 mm 2 / g ~ approx. 3m 2 / g total surface area In some embodiments, the ceramic article has a volume of about 0.4 m 2 / g ~ approx. 1.5m 2 In some embodiments, the ceramic article has a total surface area of about 0.5 m 2 / g~ Approximately 0.85m 2 / g total surface area.
[0029] We now describe the method used to measure the surface area of a ceramic article. Using a sorption analyzer, a Brunauer-Ehrlich method was performed using liquid nitrogen at 77°K for five measurements. The ratio of each ceramic article was calculated according to the Brunauer-Emmett-Teller (BET) method. Specific Surface Area (SSA) (also referred to herein as "surface area") This method was used to determine the SS of thermally stable materials with type II or type IV nitrogen sorption isotherms. This procedure can be used to determine A. Guidelines set by the International Union of Pure and Applied Chemistry (IUPAC) This is also incorporated into the ASTM and ISO standards referenced below. : Thommes, M. et al., Physisorption of gases ,with special reference to the evaluation n of surface area and pore size distribution tion(IUPAC technical report).Pure Appl.Chem.,87(9-10 )(2015), pp.1051-1069.Stephen Brunauer,P. H. Emmett,and Edward Teller,Adsorption of Gases in Multimolecular Layers.J.Am.Che m.Soc.1938,60,2,309-319.ASTM D3663-20 an d ASTM C1069-09.ISO 9277:2010.
[0030] The surface area measurements included in this application were performed using a Micromeritics ASAP 2420 Or use an ASAP 2460 with a 20cc valve filled to the maximum level The test tube was used. The sample was degassed at 250 °C for 2 h, then cooled and refilled with nitrogen. The sample tube was then loaded into the analysis port and the BET analysis was performed. The calculation was performed using the following relative pressures: 0.100, 0.125, 0.175, Relative pressure in the range of 0.05 to 0.30, with a target of 0.225 and 0.270 P / Po Five data points of N2 sorption at force (P / Po) were used.
[0031] In another embodiment, the ceramic article is about 0.5 mm 2 / g, approx. 0.6m 2 / g, about 0 .7m 2 / g, approx. 0.8m 2 / g, approx. 0.9m 2 / g, approx. 1m 2 / g, approx. 1.1m 2 / g , about 1.2m 2 / g, approx. 1.3m 2 / g, approx. 1.4m 2 / g, approx. 1.5m 2 / g, approx. 1. 6m 2 / g, approx. 1.7m 2 / g, approx. 1.8m 2 / g, approx. 1.9m 2 / g, approx. 2m 2 / g, Approximately 2.1m 2 / g, approx. 2.2m 2 / g, approx. 2.3m 2 / g, approx. 2.4m 2 / g, approx. 2.5 m 2 / g, approx. 2.6m 2 / g, approx. 2.7m 2 / g, approx. 2.8m 2 / g, approx. 2.9m 2 / g , or about 3.0 m 2 / g total surface area.
[0032] As used herein, the "water absorption rate" of a carrier is determined using the following process: Two 100 gram lots of support were weighed using an analytical balance. Dry weights were recorded and the total dry weight (DW) of the combined lots was calculated. The set was then inserted into two stainless steel swings, each measuring 80 mm long x 60 mm wide x 70 mm high. The basket was placed in one of the 0.889 mm (0.035 in) diameter, and is managed by Eppendorf North America (Hauppauge Eppendorf Swing Bass available from 100% pure copper wire suitable for use with the ket Rotor A-4-62 centrifuge Constructed from mesh stainless steel screen. Filled wire basket is placed in vacuum chamber. The support was placed in a chamber and a vacuum was pulled to 25 mmHg for 2 minutes until the support was completely covered. Water was poured into the carrier. Vacuum was again pulled to 25 mmHg and held for 2 minutes. The vacuum was released. The chamber was returned to atmospheric pressure and left for 2 min. The filled wire basket was placed in an Eppe Place in a centrifuge using the . The filled basket was rotated at 300 revolutions per minute (rpm) for a total of 1 min. The basket was spun for the spin time. The supports were then emptied from the basket and weighed in a single batch, the weight of which was previously recorded. The centrifuge weight (CW) of the combined lot was ) by weighing the pan with the loaded carrier thereon and subtracting the weight of the pan. The water absorption rate was calculated by subtracting the dry weight (DW) from the centrifuged weight (CW), This was then determined by dividing by the dry weight (DW) and multiplying by 100.
[0033] As used herein, the packing density of a powder is determined as follows: Using a 1 L measuring cylinder, weigh the contents of measuring cylinder (A) to the nearest 0.01 g, then Place it on the platform of the automatic tapping density analyzer and secure it in place. Add 1000 samples to the volume of the measuring cylinder. Set and start tapping. After 1000 taps, set the sample volume (V) Read and record. Volume should be measured to within 0.5 mL. Weigh out the Linder (B) to the nearest 0.01 g. The tapped density is then calculated by multiplying the weight of the powder ( The volume of the blood vessel can be calculated as:
[0034] In one embodiment, the ceramic article comprises a continuous alumina matrix and a plurality of discrete regions. and a dispersed alumina phase distributed within the matrix as a 0.3 cm 3 / g~0.6cm 3 / g and a total pore volume of 0.5 cm 2 / g~0.85cm 2 / g and a majority of the plurality of discrete regions each having a total surface area of about 10 μm to about 150 μm. The continuous alumina matrix has a ZnI2 dye penetration test value of 10% or more. The dispersed alumina phase has a ZnI2 dye penetration test value of 5% or less and has a diameter of about 0.6 mm to about A ceramic having a first dimension of 1.5 mm and a second dimension of about 0.45 mm to about 1 mm. In the cross-section of the article, the dispersed alumina phase comprises 5% to 50%, more preferably 8% to 10% of the cross-sectional area. 40%, and even more preferably 10% to 30%.
[0035] The present disclosure also provides a catalyst comprising a metal deposited on the ceramic article described herein. In one embodiment, the metal is silver deposited on the ceramic article described herein. The present disclosure relates to a catalyst comprising a support and a first alumina powder. By varying the ratio between the amount of the first alumina powder and the amount of the second alumina powder, the amount of gold loaded on the article can be adjusted. The dispersed phase is less porous than the continuous matrix (dispersed phase) and therefore The dispersed phase is more dense than the continuous matrix (as reflected by the lower ZnI2 penetration test value of the dispersed phase). Thus, the metal catalyst loading is lower than that of the continuous matrix in the ceramic article. By increasing the ratio of dispersed phase to catalyst, the loading of metal catalyst can be reduced. Conversely, by decreasing the ratio of dispersed phase to continuous matrix in a ceramic article, This allows the loading amount of the metal catalyst to be increased.
[0036] In order to produce the articles of the invention, certain physical and chemical properties, specifically first and second and the surface area of the second alumina and d 50 The particle size can be controlled and adjusted. Powders useful for this construction can be selected using the information in Table 1 and the following description as a guide. .
[0037] [Table 1] Preferably, the first alumina powder has a particle size of 0.2 to 100 microns, more preferably 2 to 100 microns. 20 microns, most preferably 5 to 10 microns 50 It is alpha alumina with a particle size. The first alumina powder has a maximum firing temperature of about 1600°C and a surface area of 1 to 20 m 2 / g, preferably 1 to 5 m 2 / g, more preferably 1 to 2m 2 / g The first alumina powder may be selected based on the internal porosity of the particles and the geometric surface area of the particles. The surface area of the porous material is a measure of the surface area that is provided to the porous material, and may include any internal porosity that contributes significantly to the total surface area. The alumina powder in step 1 should not be fused alumina or platelet alumina. When used, plate alumina is aluminum oxide heated to a temperature above 1,650°C. As used herein, solubility is defined as a crystalline tablet. Fused alumina is melted in an electric arc furnace, cooled, crushed, and recast into the desired shape. Calcined alumina is defined as calcined alumina that has been heated to a temperature above 1,050°C. The aluminum oxide has been treated to remove nearly all of the chemically bound water.
[0038] Preferably, the second alumina is selected from the group consisting of platelet alumina and fused alumina. The second alumina powder is alpha alumina, which is the most highly sintered, as in the case of fused alumina. The synthesis temperature may be higher than the melting point of alumina, or, as in the case of platelet alumina, the alumina melting temperature may be higher than the melting point of alumina. The second alumina is alpha alumina made by a process that may have a melting point slightly lower than that of alumina. Mina's d 50 The particle size is preferably 5 to 400 microns, more preferably 10 to 200 microns, and most preferably The second alumina powder may preferably be 40 to 150 microns. The second alumina powder has a very small internal diameter because it is sintered at a temperature close to or above its melting point. The lack of internal porosity is due to the absence of internal porosity contributing to the total surface area. This results in a lower total surface area than the first alumina powder of similar particle size. The second alumina powder, which has not been subjected to the grinding process for the purpose of 2 / g, Preferably 0.10 to 0.50 m 2 / g, more preferably 0.14 to 0.30 m 2 / g Has a surface area.
[0039] d of the second alumina 50 d of first alumina versus particle size 50 By selecting the particle size ratio is used to control the total surface area of an article made from the first and second alumina powders. In principle, the particle size of the first alumina powder is smaller than the particle size of the second alumina powder. It should be much smaller. Preferably, the d of the first alumina 90 The second Al Mina's d 10 More preferably, the d of the first alumina should be less than 95 The second of alumina 05 Even more preferably, the d9 of the first alumina should be less than 1. 9 is the second alumina d 01 Preferably, the first and second The particle size distribution of the alumina should be unimodal.
[0040] More specifically, the d of the first alumina powder 50 Particle size vs. d of the second alumina powder 50 grain The diameter ratio is 1:4 to 1:40, preferably 1:5 to 1:20, and more preferably 1:8 to 1 These ratios may be d : 15 of the second alumina powder. 50 The particle size of the first alumina Powder d 50 The particle size is 40 times or less, preferably 20 times or less, and more preferably 15 times or less. This ratio also indicates that the d 50 The particle size is 1 of alumina powder 50 At least 4 times, preferably at least 5 times, larger than the particle size. It is indicated that it should preferably be at least 8 times larger.
[0041] Absolute d of the first and second alumina powders 50 In addition to the particle sizes and their ratios, the first The surface area of the alumina and second alumina powders can be used to produce powders useful for making the articles of the present invention. In principle, the surface area per gram of the first alumina powder is approximately equal to that of the second alumina powder. It must be much greater than the surface area per gram of Lumina powder. The ratio of the surface area of the first alumina powder to the surface area of the second alumina powder is 7:1 to 15. :1, preferably 5:1 to 10:1, and more preferably 4:1 to 5:1. The ratio is preferably such that the surface area of the first alumina powder is 15 times or less than the surface area of the second alumina powder. It is shown that the ratio should be preferably 10 times or less, and more preferably 5 times or less. The ratio also requires that the surface area of the first alumina powder is less than the surface area of the second alumina powder. should be at least 7 times, preferably at least 5 times, and more preferably at least 4 times greater. Indicates that there is no
[0042] The particles of the second alumina are sometimes referred to herein as the dispersed phase and form a continuous matrix. The second alumina particles are randomly distributed throughout the alumina phase. At least 70% of the secondary alumina particles visible in the SEM micrographs at If the second alumina particles do not appear to be in contact with other second alumina particles, they do not form a continuous phase. It is believed that the second alumina particles completely or partially surround the second alumina particles. The second alumina particles are physically isolated from the other second alumina particles by a plurality of first alumina particles. It may appear that
[0043] Alumina type, specific d 50 so particle size and their ratio, as well as the first and second The weight ratio of the powder is such that the cross-sectional area of the second alumina particles is at least 5-50% of the total cross-sectional area of the article. %, more preferably 8% to 40%, and even more preferably 10% to 30%. The weight ratio of the first alumina powder to the second alumina powder can be controlled to be , 15:1 to 1:1. 14:1, 12:1, 10:1, 8:1, 7:1, 6: Intermediate ratios of 1, 5:1, 4:1, 3:1 and 2:1 are feasible.
[0044] In one embodiment, the first alumina powder is at least 85 weight percent alpha-alumina. More preferably, the first aluminum The mina powder is at least 90 percent, 95 percent, or 99 percent by weight. In one embodiment, the second alumina powder is fused alumina only. The ceramic may be only platelet alumina or a mixture of platelet alumina and fused alumina. The present invention relates to a method for making a plastic article.
[0045] As described herein, particle size was measured using Horiba Particles LA-950 Laser Scattering Particles. The particle size distribution is determined by laser scattering using a size distribution analyzer. The analyzer has a resolution of 0.01 microns to Uses the principles of Mie scattering theory to measure particle size and distribution in the 3000 micron range In this specification, "d 50 The median particle size referred to as "" is smaller than the median particle size listed. This method expresses the particle size at which the spherical equivalent volume of the larger particle and the smaller particle are equal. Adding arvan® solution and dispersing particles by sonication. , thus involving the breakdown of secondary particles into primary particles. This ultrasonic treatment involves the 50 value This was continued until no further changes were observed, and this was followed by Horiba LA-950 capsules. When using a diameter analyzer, sonication for 1-5 minutes is typically required.
[0046] In some embodiments, the method for making a ceramic article includes adding a bonding material, e.g. , magnesium silicate. If desired, in preparing the ceramic article, One or more optional additives may be included, for example to facilitate the formation of the compact and / or or one or more additives to modify one or more properties of the resulting ceramic article. Suitable additives include binders (e.g., polyolefins). cellulose, alkaline earth metal compounds such as magnesium silicate and and calcium silicates, and alkali metal compounds), extrusion aids (e.g., petrolatum, Hydrogenated oil, synthetic alcohol, synthetic ester, glycol, starch, polyolefin glycerides, polyethylene glycols, and mixtures thereof), a solvent (e.g., water), deflocculating acid ( For example, monofunctional acids containing 1 to about 5 carbon atoms, such as formic acid, acetic acid, and / or propanoic acid. (functional aliphatic carboxylic acids), halogenated monofunctional aliphatic carboxylic acids containing 1 to about 5 carbon atoms Carboxylic acids (e.g., mono-, di- and trichloroacetic acid, etc.), fluxes, binders, dispersants, These include burn-in materials, also known as "pore formers," and strength-enhancing additives. Any of a wide variety of known carrier additives may be included, without limitation. For example, methods of preparation and selecting suitable additives in appropriate amounts taking into consideration the desired properties of the resulting ceramic article. It is within the capabilities of one skilled in the art to do so.
[0047] In some embodiments, the process includes the use of formic acid. Formic acid reduces the amount of particles in the mixture. It may function to stabilize the dispersion. In some embodiments, formic acid is present at about 1% (w / w% ), about 1.5% (w / w%), about 2% (w / w%), about 2.5% (w / w%), about 3% ( %, about 3.5% (w / w%), about 4% (w / w%), about 4.5% (w / w%), Approximately 5% (w / w%), approximately 5.5% (w / w%), approximately 6% (w / w%), approximately 6.5% (w / %, about 7% (w / w%), or about 7.5% (w / w%).
[0048] In some embodiments, the mixture further comprises one or more thermally decomposable materials. 2% (w / w%) to about 40% (w / w%), or about 5% (w / w%) to about 30% (w / w%) %. The thermally decomposable material may function as a pore former. As used herein, a thermally decomposable material is a solid in particulate form. The material is a mixture of alumina powder and at least two different types of alumina prior to the heating step. The individual particles of the pyrolysable material are mixed with the Lumina green mixture. The individual particles of the pyrolysable material occupy a small space during the heating and / or sintering steps. The pores in the ceramic article forming the carrier are removed by pyrolysis during the process. Pores may also be described as a plurality of voids distributed throughout the ceramic article. In some embodiments, the majority of the pores created by the use of thermally decomposable materials. The components are contained within a continuous matrix. For example, they can be made by using pyrolyzable materials. At least 50%, at least 60%, at least 70%, at least 80% of the pores Or at least 90% is contained within a continuous matrix.
[0049] The pyrolyzable material does not have to be any of the other components used to make the ceramic article. Similarly, the thermally decomposable material should not dissolve any of the other ingredients. No. The pyrolyzable material occupies a volume prior to the heating step, and the space occupied by the material Since the pore formers remain largely unoccupied after the heating step is completed, the material is The thermally decomposable materials useful in the process of the present invention are typically organic materials. Preferably, the chemical formula of the organic material includes carbon and hydrogen. The thermally decomposable material may be a natural or natural material or a mixture thereof. The material may be an organic material having a decomposition temperature below the sintering temperature of the mina powder. It is ensured that the material is at least partially removed prior to or simultaneously with sintering of the alumina powder. To facilitate decomposition, the chemical formula of the pyrolyzable material is preferably carbon, water, The decomposition temperature may be reduced by the presence of oxygen.
[0050] In some embodiments, the mixture may include one or more additives that result in the formation of pores during burnout. Also included herein are naturally occurring thermally decomposable materials. Degradable materials do not contain polymers or other processing aids in the formulation. Rather, they are naturally The pyrolysable material present may be used to facilitate the shaping of the shaped body and / or to enhance the thermal stability of the resulting ceramic. Optionally included in the preparation of ceramic articles to alter the porosity of the article. Typically, burnout materials are materials that are dried, fired, and / or Or burn out, sublime, or volatilize during sintering. Examples of suitable burnout materials are Nuts include pecans, cashews, walnuts, peaches, apricots, and filberts. Examples of suitable fermentation products include, but are not limited to, crushed shells of corn. Any other naturally occurring thermally decomposable material may be used. A pore volume of 0.1 mL / g or less in the resulting ceramic article is considered to be a burnout material. In some embodiments, the naturally occurring thermally decomposable material is is not included.
[0051] The thermally decomposable material may be a synthetic material. The synthetic material may be a polymeric material. While not wishing to be bound by any particular theory, as used herein, Synthetic materials are intended to exclude naturally occurring thermally decomposable materials. They can also be formed using emulsion polymerization, including suspension polymerization, in which case they can be used directly as thermally decomposable materials. This is often preferred because it results in a polymer in the form of fine particles that can be used for purposes of this invention. The material may be formed using anionic polymerization. The polymeric material may be an olefin polymer or and copolymers, such as polyethylene, polypropylene, polystyrene, polyvinyl alcohol, ethylene-vinyl acetate and ethylene-vinyl alcohol copolymers, diene polyvinyl chloride, Polymers and copolymers, e.g., polybutadiene, EPDM rubber, styrene-butadiene copolymers, and butadiene-acrylonitrile rubber, polyamides, e.g. -6 and polyamide-66, polyesters such as polyethylene terephthalate Preferably, the polymeric material is a hydrocarbon polymer such as a polyolefin, more preferably Alternatively, it may be polypropylene.
[0052] Pyrolyzable materials are scrubbed to restrict the size of individual particles to a specific particle size range. If desired, the particles within the first particle size range may be screened or otherwise selected. A first pyrolyzable material having particles is mixed with a second pyrolyzable material having particles within a second particle size range. In combination with the materials, a multimodal distribution of pore sizes in the porous ceramic article can be obtained. The particle size range limit is determined by the size of the pores formed in the porous ceramic article of the carrier. It is determined.
[0053] In some embodiments, the mixture comprises hydroxypropyl methylcellulose, vinyl chloride copolymer, vinyl acetate copolymer, olefin polymer, olefin copolymer, poly Ethylene, polypropylene, polystyrene, polyvinyl alcohol, ethylene vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, diene polymers, diene copolymers ethylene propylene diene monomer, polybutadiene Monomer, EPDM) rubber, styrene-butadiene copolymer, butadiene acrylonitrile Rubber, polyamide, polyamide-6, polyamide-66, polyester, polyethylene terephthalates, hydrocarbon polymers, polyolefins, and polypropylenes. The one or more polymers or copolymers may further comprise may function as a lubricant and / or a pore former.
[0054] The support body may be formed by any convenient forming process, such as spray drying, agglomeration, or pressing. The mixture may be formed by extrusion, preferably by extrusion of the mixture. For example, see U.S. Pat. Nos. 5,145,824, 5,512,530, and 5,512,530. Nos. 5,384,302, 5,100,859, and 5,733,842 Reference can be made to the following technical papers, each of which is incorporated herein by reference. To facilitate the molding process, especially extrusion, the mixture is preferably 2 to 25% w / w, more preferably 5 The composition may be suitably blended with up to 15% w / w of a processing aid, also referred to by the term "extrusion aid." The processing aids that are mentioned are, for example, in the Kirk-Othmer Encyclopedia of Chemical Technology,”4th edition,Volu This is known in the art, as described in J. Med. 5, p. 610. Suitable processing aids are typically liquid or greasy substances such as petrolatum, hydrogenated oils, It is a synthetic alcohol, a synthetic ester, a glycol, or a polyolefin oxide. Acids may also be used, for example in amounts up to 0.5% w / w%, more typically 0.01 to 0.5% The total weight of the alumina in the mixture is calculated by adding 100% of the alumina in the mixture. and zirconia, etc., based on the total weight of the ceramic.
[0055] In some embodiments, the process includes extruding the mixture prior to firing and / or sintering. In some embodiments, the process further comprises adding the mixture prior to firing and / or sintering. For example, the mixture may be formed into a carrier. Generally, the size of the supports is determined by the dimensions of the reactor in which they are deposited. However, in general it is highly preferred to use carriers in the form of cylinders, spheres, donuts, etc. It has been found to be convenient. The cylinder may be solid or hollow, straight or curved. They may be 4-20 mm long, typically 5-15 mm long, 4-20 mm long, typically Typically, it has an outer diameter of 5 to 15 mm and an inner diameter of 0.1 to 6 mm, typically 0.2 to 4 mm. The cylinder may have a length to outside diameter ratio in the range of 0.5 to 2, typically 0.8 to 1.2. obtain.
[0056] The formed parts can be produced in a variety of shapes, including cylindrical, spherical, annular, or multi-lobal. For example, shaped pellets can be made by extruding a continuous rod of paste and then The paste may be formed by cutting the rod into pellets of the desired size. The rod is extruded through a die of a certain shape and then cut into pellets of a certain cross section. ring-based shaped structures of any desired configuration, such as "wagon wheels" Or any structure with a constant cross section, such as multi-lobe structures and small honeycombs. Other extrusion shapes may be formed. The shaped article may also be in the form of a large honeycomb monolith. However, the extrusion / pressing process is not limited to these shapes. , may have an outer diameter, or average width if non-circular, of about 0.8 to about 25 mm, although other sizes may be used. Reference may be made to U.S. Patent Application Publication No. 2012 / 0171407, No. 6,399,633, which is incorporated herein by reference for further explanation of multi-lobe carriers. Additionally, the size of the ceramic article carrier is generally not limited and may be used in catalytic reactors, e.g. For example, any size suitable for use in an ethylene oxidation reactor. The item carrier has a length of 5 to 15 mm, an outer diameter of 5 to 15 mm, and a thickness of 0.2 to 4 In some embodiments, the ceramic article carrier may be cylindrical with an inner diameter of 1.5 mm. , the ceramic article carrier may have a length to outer diameter ratio of 0.8 to 1.2. For example, the ceramic article carrier may be in the form of a hollow cylinder with a wall thickness of .about.7 mm. Consider the type and configuration of the catalytic reactor used, e.g., the length and inner diameter of the tubes within the catalytic reactor. Thus, selecting a suitable shape and size of the ceramic article carrier is within the scope of the present disclosure. It is within the ability of one skilled in the art to enjoy such a technique.
[0057] In some embodiments, the process further comprises drying the formed body. The formed body may be dried to remove at least a portion of the water, if any, present. Water is converted to steam during the heating step described below and can adversely affect the physical integrity of the compact. Drying may occur after preparation of the mixture and optional shaping of the mixture into multiple bodies. The drying step can be performed by controlling the heat profile of an oven or kiln. Drying can be combined with a heating step by heating the mixture at temperatures between 20°C and 400°C. The heating temperature is 30° C. to 300° C., typically for up to about 100 hours, preferably for about 5 minutes to about 50 hours. Typically, drying is performed so that the mixture contains less than 2% w / w water. This is carried out to the extent that
[0058] Firing and / or sintering generally refers to a process carried out at a sufficiently high temperature for a sufficiently long time, for about The reaction is carried out for a period of up to 100 hours, preferably from about 5 minutes to about 50 hours. In some embodiments, the calcination and / or sintering step comprises calcining at least two aluminas. At least 50%, or at least 75%, or at least 85%, or at least 90% or at least one temperature, one pressure, and one or more pressures sufficient to sinter at least 95%. In some embodiments, the process may be carried out for a period of time above 120° C. In some embodiments, the process includes heating the mixture at a temperature of 160° C. 0° C. In some embodiments, the process includes heating to a temperature of about 1200 The calcination and / or sintering may include heating the mixture at a temperature of from about 1600° C. to about 1600° C. Any gas, including but not limited to nitrogen, argon, helium, carbon dioxide, water vapor, etc. In an embodiment where the compact further comprises an organic burnout material, At least one of the heating and / or calcination is performed in an oxidizing atmosphere, such as an oxygen-containing atmosphere. As used herein, calcination and / or Sintering refers to the process of firing and solidifying a green body made and formed from powder particles. The particles bond to adjacent particles to form a strong formation of alumina particles. The voids are , may be present between and / or within the grains and collectively contribute to the porosity of the ceramic article.
[0059] After firing and / or sintering, the resulting ceramic article may optionally be subjected to a thermal deactivation step prior to deposition of an active catalytic material. It may be optionally cleaned and / or treated, as well as formed into a ceramic article, if desired. Any raw materials used to make the product may be cleaned and / or treated prior to firing and / or sintering. Any method known in the art for cleaning and / or treating may be used to obtain such a method. As long as they do not adversely affect the performance of the support or catalyst being used, they may be used in accordance with the present disclosure. For a description of such a method, see U.S. Pat. Nos. 6,368,998 and 7,232, 918, 7,741,499, and WO 2007 / 092022 (which (each of which is incorporated herein by reference). If washing is desired, Washing is typically carried out at temperatures ranging from 15° C. to 120° C. for up to about 100 hours, preferably The cleaning may be carried out over a period of about 5 minutes to about 50 hours. The cleaning may be carried out either continuously or batchwise. Examples of suitable cleaning solutions include water, e.g., deionized water, one or more Aqueous solutions containing salts, e.g., ammonium salts, amine solutions, e.g., ethylenediamine, water and combinations thereof. Similarly, suitable aqueous solutions may be acidic, basic, or neutral. The volume of the cleaning solution may vary depending on the The ceramic article may be impregnated until the incipient wetness point of the ceramic article is reached. Alternatively, a larger volume may be used and the excess of solution removed, e.g., by centrifugation. The wet ceramic article may then be removed from the wet ceramic article following any further cleaning and / or processing steps. In some cases, it is preferred to dry or calcinate the ceramic article prior to deposition of the catalyst article. The ceramic article may be heated in a stream of air at a temperature of, for example, about 80° C. to about 400° C. for a sufficient period of time. It may be dried.
[0060] The formed ceramic article can be used directly as a catalyst or in the form of a compact. During or after formation, the catalyst is impregnated with a solution of catalytically active material, optionally followed by suitable post-treatment. After activation, they can also be used as catalyst supports. Transition metal elements such as those from groups VB, VIIIB and IB of the periodic table, e.g. In some embodiments, the metal may be, for example, silver, nickel, nickel-based silver ... Catalytically active metals include ruthenium, cobalt, ruthenium, and / or iron. Silver is particularly preferred. Exemplary applications for which the carriers may be used include direct ethylene oxidation. However, it is contemplated that the ceramic articles may be used in any application. EXAMPLES
[0061] A process for preparing a support for use in epoxidation reactions is incorporated herein by reference. Incorporated U.S. Patent No. 5,100,859 and U.S. Patent No. 6,831,037 No. 5,100,859, and numerous other publications. See the disclosure in column 2, line 6 to column 6, line 43 of the present invention. Certain embodiments of the invention will now be described in further detail. These examples are provided for illustrative purposes only. Carrier A is provided as a comparative example and should not be construed as limiting the invention. Carriers B, C, D, and E are embodiments of the invention described herein.
[0062] Carrier A (Comparative Example) Carrier A, the comparative carrier in this disclosure, is a carrier disclosed in U.S. Pat. No. 5,100,859 (German: was prepared according to the teachings of Carrier L disclosed in US Pat. No. 6,333,363, with the following modifications: The only alumina powder used in Comparative Support A was 7.7 microns d 50 Particle size, 1.4 m 2 1. The first plurality of aluminum alloys have a surface area of 0.5 μm / g and a packing density of 0.78 g / cc. The first plurality of alumina particles are referred to as alumina particles. A first plurality of alumina particles, zirconia particles, and a mixture of lumpy shell powder, boric acid, and an extrusion aid. The combination of Carrier A, magnesium silicate, and walnut shell flour is referred to herein as a dry mix of Carrier A. The combined weight of the dry mixture of water, boric acid, and extrusion aid is In the specification, it is defined as a wet mixture of carrier A, which is extruded, dried and calcined. In the carrier A, the first plurality of alumina particles were dispersed throughout the carrier. Carrier A did not contain a dispersed phase. The physical and chemical properties of the fired cylinder, which may be referred to as a block article, carrier, or support, are as described above. The water absorption of Carrier A was determined using the analytical techniques described above. The water absorption of Carrier A was 48.7 g / g and the surface area was 0.78m 2 It was.
[0063] Carrier B (one embodiment of the present invention) In one embodiment of the present invention, Carrier B is 10 weight percent of the dry mixture of Carrier A, The alumina particles are replaced with an equal mass of a plurality of fused alumina particles, referred to herein as the second plurality of alumina particles. The comparative example described immediately above was repeated except that the dry mixture of Carrier B was replaced with Carrier B. The second plurality of carriers were prepared by following the process used to prepare carrier A. Lumina particles have a diameter of 119.7 microns. 50 , 0.2m 2 / g surface area, and 2.1 g / The dry mixture of Carrier B was combined with water, boric acid, and an extrusion aid. A wet mixture of the carrier B is then extruded to form a hollow cylinder, which is The calcined cylinders were dried and calcined. The physical and chemical properties of the calcined cylinders were measured. Carrier B The water absorption rate is 46.70 g / g and the surface area is 0.74 m2 It was.
[0064] Carrier C (one embodiment of the present invention) Carrier C, an embodiment of the present invention, is a mixture of 25 weight percent of the dry mixture of Carrier A, The alumina particles are replaced with an equal mass of a plurality of fused alumina particles, referred to herein as the second plurality of alumina particles. Carrier A was prepared as described above, except that it was replaced with Carrier B, thereby forming a dry mixture of Carrier C. The second plurality of alumina particles was prepared by following the process used to prepare the second plurality of alumina particles. , d of 119.7 microns 50 , 0.2m 2 / g surface area and a packing density of 2.1 g / cc The dry mixture of Carrier C was combined with water, boric acid, and an extrusion aid to form Carrier B. A wet mixture of part C is prepared and then extruded to form a hollow cylinder which is then dried; The physical and chemical properties of the fired cylinders were measured. The water absorption rate of carrier C was 4 2.86g / g and surface area is 0.63m 2 It was.
[0065] Carrier D (one embodiment of the present invention) Carrier D, an embodiment of the present invention, is a dry mixture of Carrier A, which is 40 weight percent: The alumina particles are replaced with an equal mass of a plurality of fused alumina particles, referred to herein as the second plurality of alumina particles. Carrier A was prepared as described above, except that it was replaced with Carrier D, thereby forming a dry mixture of Carrier D. The second plurality of alumina particles was prepared by following the process used to prepare the second plurality of alumina particles. , d of 119.7 microns 50 , 0.2m 2 / g surface area and a packing density of 2.1 g / cc A dry mixture of Carrier D was combined with water, boric acid, and an extrusion aid to form Carrier B. A wet mixture of body D is prepared and then extruded to form a hollow cylinder which is then dried; The physical and chemical properties of the fired cylinders were measured. The water absorption rate of carrier D was 3 7.70 g / g and surface area is 0.53 m 2 It was.
[0066] Carrier E (one embodiment of the present invention) Carrier E, one embodiment of the present invention, is a dry mixture of Carrier A, 50 weight percent of which is: The alumina particles are replaced with an equal mass of a plurality of fused alumina particles, referred to herein as the second plurality of alumina particles. Carrier A was prepared as described above, except that it was replaced with Carrier E, thereby forming a dry mixture of Carrier E. The second plurality of alumina particles was prepared by following the process used to prepare the second plurality of alumina particles. , d of 119.7 microns 50 , 0.2m 2 / g surface area and a packing density of 2.1 g / cc The dry mixture of Carrier E was combined with water, boric acid, and an extrusion aid to form Carrier E. A wet mixture of body E is prepared and then extruded to form a hollow cylinder which is then dried; The physical and chemical properties of the fired cylinders were measured. The water absorption rate of carrier E was 3 5.64g / g and surface area is 0.43m 2 It was.
[0067] FIG. 1 shows that the surface area and water absorption of the support depend on the amount of dispersed phase alumina in the support. Curve 101 is calculated as the surface area of the carrier and the percentage of the dry mixture of carrier A. Curve 102 shows the relationship between the water absorption rate of the carrier and the weight percent of the dispersed phase. The relationship between the weight percent of the dispersed phase calculated as a percentage of the dry mixture of A is shown. .
[0068] 2A-2C show the microstructure of a ceramic article of the present invention. Back-scattered electron (BSE) microscopy images of the first alumina powder ( The second array distributed in the regions 208, 210, and 212 of FIGS. 2A, 2B, and 2C Lumina powder phase (areas 202, 204, and 205 in FIGS. 2A, 2B, and 2C, respectively) 6) The particle size of the second alumina powder is significantly larger than that of the first alumina powder. The magnification of Fig. 2A is 100 times. The magnification of Fig. 2B is 250 times. Fig. 2C The magnification is 500x.
[0069] Figures 3A and 3B show a ceramic substrate that has been epoxy mounted and polished to a 1 micron finish. The polished cross section of the composite article shows the identification of dispersed phase particles. The samples were gold coated to prevent charging using a Zeiss Merli n Using a SEM, images were taken using an accelerating voltage of 2 keV and a beam current of 100 pA. The type of SEM used is not critical, but it is important to identify and characterize the dispersed phase. It is necessary to be able to generate images suitable for image analysis software for isolating the The SEM images are magnified 100 times for the larger diluent particles (see Figure 3A). For the smaller sized diluent particles, a magnification of 250x was obtained. Obtain a particle count of ≥ 100. Use image analysis software to identify dispersed phase particles. The National Institutes of Health (NIH) and the National Institutes of Health (NIH) have isolated and separated the IL-16 ... f Health and the Laboratory for Optical and Computational Instrumentation, im is an open source image processing program available for download at imageJ.net. Using ageJ software, the total coverage area of the dispersed phase in each image, as well as the phase distribution of each image, were measured. The type of image analysis software used is not important. and one of ordinary skill in the art is familiar with the image manipulations required to identify and isolate the dispersed phase. The area coverage of the dispersed phase was calculated using four images from carrier E and one image from carrier C. The area coverage of the dispersed phase from these images ranged from 9 to 23%. The data in Table 2 show that the area coverage of carrier C was 9.1 percent, while that of carrier E was 1.3 percent. The area coverage of the four images was approximately 20 percent.
[0070] [Table 2] ZnI2 dye penetration test values were determined using the following ZnI2 solution penetration test. First 220 g of ZnI2 was placed in 1,000 mL of water at 20°C, thereby obtaining a ZnI2 solution. A 5 g sample of the ceramic article was introduced into 100 mL of the ZnI2 solution. The container holding the ceramic article sample was placed in a vacuum chamber for 20 hours. The dried samples were then removed from the oven and dried at 50°C for 24 hours, then at 110°C for a minimum of 2 hours. The material was dried in epoxy resin within 30 minutes of removing it from the drying oven to avoid re-absorption of water. After the epoxy cured, the samples were polished to a 3 micron finish and then heated at 100°C for 30 min. It was kept in a drying oven.
[0071] SEM manufactured by Hitachi, Model S4300 and Oxford I The EDS detector, X-MaxN 150 detector, manufactured by Instruments, was used. The system model used is Aztec SEM, and Aztec version 3.3 SP1. The software was used to characterize the distribution of iodide on the alumina particles. The materials were carbon-coated to prevent charging. SEM-EDS images were taken with the parameters shown in Table 3. The photo was taken within the range of .
[0072] [Table 3] At least one of the second alumina particles and an equivalent area of the first alumina particles; A manually selected area containing the area was used to collect EDS data. The software was able to generate the concentrations of iodine and zinc in each area. Both iodine and zinc concentrations can be used to compare the amount of penetration, but iodine is more effective. It was good.
[0073] The area of the second alumina particle, which is one particle in the dispersed phase, is shown as area 402 in FIG. 4A. The amount of iodine in region 402 was determined using EDS. FIG. 4B is an EDS image showing the location of ZnI2 in FIG. 4A. The dark areas in FIG. 4B are In FIG. 4A, region 4 indicates the absence of ZnI2, and bright regions indicate the presence of ZnI2. The amount of iodine in an equivalent area of the matrix phase, identified as 01, was also determined. The amount of iodine collected represents the amount of iodide penetration in a given phase. Table 4 shows the results for two different In Table 4, the analytical data from the example of Carrier D is shown. The amount of iodide in the matrix phase is 14.68 atomic percent. The amount of iodine present in the dispersed phase was calculated based on the molecular weight of the iodine in the matrix phase. The ceramic articles of the present invention are manufactured for use as catalyst supports in amounts much less than the This is thought to correlate with the amount of catalytically active metal, such as silver, deposited on the same alumina particles. can be obtained.
[0074] [Table 4]
[0075] In Table 4, percentages refer to atomic weight percent.
[0076] The fused alumina particles are not infiltrated by ZnI2. The SEM image is shown in Figure 5A. As can be seen, the pores are clearly larger and more penetrating, distributed throughout the continuous matrix. FIG. 5B shows particles that cannot be detected by the ion beam. See particles 502, 504, and 506. 5A and 5B are EDS images showing the location of ZnI2. The dark areas in FIG. 5B are ZnI The absence of ZnI2 indicates bright areas, while the absence of ZnI2 indicates the presence of ZnI2. , demonstrating the ability to create an impermeable phase distributed in a matrix phase.
[0077] Embodiment Embodiment 1. A ceramic article comprising: (a) an alumina particle including a plurality of first alumina particles and a plurality of second alumina particles; A hard formation of the granules of both are randomly distributed throughout the hard formation. Cloth, 1) the second alumina particles have a ZnI2 dye penetration test value of 5 atomic percent or less The first alumina particles have a ZnI2 dye penetration test value of the second alumina particles. ZnI2 dye penetration test value of at least twice that of 2) the hard formation has a total cross-sectional area, and each of the plurality of particles occupies a portion of the total cross-sectional area. The cross-sectional area of the second alumina particles is 5% to 50% of the total cross-sectional area. , (b) a catalytically active metal dispersed on the first and second alumina particles. Ramic items.
[0078] Embodiment 2. The ZnI2 dye penetration test value of the first alumina is higher than that of the second alumina. 2. The article of claim 1, wherein the ZnI2 dye penetration test value is at least three times greater than the ZnI2 dye penetration test value of 1.
[0079] Embodiment 3. The ZnI2 dye penetration test value of the first alumina is higher than that of the second alumina. 2. The article of claim 1, wherein the ZnI2 dye penetration test value is at least 4 times greater than the ZnI2 dye penetration test value of 1.
[0080] Embodiment 4. The first alumina has a ZnI2 dye penetration test value of 10 atomic percent 2. The article of embodiment 1, wherein the article is greater than
[0081] Embodiment 5. The first alumina has a ZnI2 dye penetration test value of 15 atomic percent. 2. The article of embodiment 1, wherein the article is greater than
[0082] Embodiment 6. The second alumina has a dye penetration test value of 3 atomic percent or less. , The article of embodiment 1.
[0083] Embodiment 7. Dye penetration test value of the first alumina and dye penetration of the second alumina 2. The article of claim 1, wherein the ratio of the test value is at least 2:1.
[0084] Embodiment 8. The cross-sectional area of the second alumina particles is 8% to 40% of the total cross-sectional area. 2. The article of embodiment 1.
[0085] Embodiment 9: The cross-sectional area of the second alumina particles is 10% to 30% of the total cross-sectional area. , The article of embodiment 1.
[0086] Embodiment 10. Further comprising a total pore volume of about 0.2 cm3 / g to about 0.6 cm3 / g. 2. The article of embodiment 1.
[0087] Embodiment 11. A practical embodiment having a total pore volume of about 0.3 cm3 / g to about 0.5 cm3 / g. 11. The article of embodiment 10.
[0088] Embodiment 12. The total pore volume is from about 0.35 cm3 / g to about 0.5 cm3 / g. 11. The article of embodiment 10.
[0089] Embodiment 13. The catalytically active metal is selected from the group consisting of silver, platinum, palladium, nickel, and copper. 2. The article of embodiment 1, selected from the group consisting of:
[0090] Embodiment 14. A hard formation of alumina particles and a catalytically active metal in contact with the particles. and a process for producing a ceramic article, the process comprising: (a) a first plurality of particles having a known weight and a d50 particle size of about 0.2 to 100 microns; Providing alpha alumina particles; (b) a known weight of alumina selected from the group consisting of fused alumina and platelet alumina; providing a plurality of second alpha alumina particles, the second alumina particles having an average particle size of about The d50 particle size of the first alumina particles is 5 to 400 microns, and the d50 particle size of the second alumina particles is The ratio of the weight of the first alumina to the d50 particle size of the first alumina is 1:4 to 1:40. a weight ratio of the first alumina to the second alumina is 1:1 to 15:1; (c) mixing the plurality of alumina particles, thereby forming a mixture. mixing the particles so that they are randomly distributed throughout the mixture; (d) forming the mixture into a plurality of malleable articles; (e) heating the malleable article to a sintering temperature of the alumina particles, thereby forming each malleable article. forming a malleable article from a hard formation of alumina particles, the particles in each of the plurality of particles being , randomly distributed throughout the hard formation; and (f) depositing a catalytically active metal on the first and second alumina particles. Hmm, the process.
[0091] Embodiment 15. The ratio of the weight of the first alumina to the weight of the second alumina is 1 15. The process of embodiment 14, wherein the ratio of the ration is from 1 to 10:1.
[0092] Embodiment 16. The ratio of the weight of the first alumina to the weight of the second alumina is 1 15. The process of embodiment 14, wherein the ratio of the ration is 1 to 5:1.
[0093] Embodiment 17: d50 particle size of first alumina particles and d50 particle size of second alumina particles The process of embodiment 14, wherein the ratio of is 1:5 to 1:20.
[0094] Embodiment 18: d50 particle size of first alumina particles and d50 particle size of second alumina particles The process of embodiment 14, wherein the ratio of is 1:8 to 1:15.
[0095] Embodiment 19. The second alumina particles have a d50 particle size of about 10 to 200 microns. 15. The process of embodiment 14, comprising:
[0096] Embodiment 20. The second alumina particles have a d50 particle size of about 40 to 150 microns. 15. The process of embodiment 14, comprising:
[0097] Embodiment 21 The plurality of first alumina particles has an area of 1.0 m2 / g to 20.0 m2 / g 15. The process of embodiment 14, having a surface area of 1.0 g.
[0098] Embodiment 22. The plurality of first alumina particles has an area of 1.0 m2 / g to 5.0 m2 / g 15. The process of embodiment 14, having a surface area of
[0099] Embodiment 23. The plurality of first alumina particles has an area of 1.0 m2 / g to 2.0 m2 / g 15. The process of embodiment 14, having a surface area of
[0100] Embodiment 24. The plurality of second alumina particles has an area of 0.01 m2 / g to 2.00 m2 15. The process of embodiment 14, having a surface area of 1 / g.
[0101] Embodiment 25. The plurality of second alumina particles has an area of 0.10 m2 / g to 0.50 m2 15. The process of embodiment 14, having a surface area of 1 / g.
[0102] Embodiment 26. The plurality of second alumina particles has an area of 0.14 m2 / g to 0.30 m2 15. The process of embodiment 14, having a surface area of 1 / g.
[0103] Embodiment 27. An embodiment in which the second alumina particles consist essentially of fused alumina. The process according to embodiment 14.
[0104] Embodiment 28. The method of embodiment 14, wherein the second alumina particles are made of fused alumina. The process described.
[0105] Embodiment 29. An embodiment in which the second alumina particles consist essentially of platelet alumina. The process according to embodiment 14.
[0106] Embodiment 30. The method according to embodiment 14, wherein the second alumina particles are made of platelet alumina. The process described.
[0107] Embodiment 31. The second alumina particles are essentially made of platelet alumina and fused alumina. 15. The process of embodiment 14,
[0108] Embodiment 32. The second alumina particles are made of platelet alumina and fused alumina. 15. The process of embodiment 14.
[0109] Unless otherwise defined, all technical and scientific terms used herein are It has the same meaning as generally understood by a person skilled in the art to which this invention belongs. All patents and publications mentioned therein are incorporated by reference in their entirety.
[0110] Ranges are used herein to describe physical or chemical properties, such as molecular weight or chemical formula. As used in the specification, all combinations and parts of ranges and specific embodiments therein are intended to be encompassed. When referring to a number or numerical range, the term "about" is intended to include any and all subgroups. Use of the term "numerical range" means that the stated number or range of values is within experimental variability (or statistically significant). These are approximations (within experimental error) and therefore mean that numbers or numerical ranges may vary. The variation is typically 0% to 5% of the stated number or range of values.
[0111] "Comprising," "consisting essentially of," and The transitional phrases "consisting of" and "consisting of" are used in the appended claims. When used in this form and in its amended form, the scope of any further unrecited claims is Regarding the exclusion of elements or steps, if any, from the scope of the claims The term "comprising" is used to define the scope of the claims. The present invention is intended to be a one-end application and does not include any additional unrecited elements, methods, or steps. The term "consisting of" does not exclude any component, structure, or material. excludes any element, step or material other than those specified in the "consisting essentially of" means "essentially composed of" or "excludes impurities normally associated with the specified material." The term "sensibly of" is used to define a claim with respect to a specified element, step, or materials, and which do not materially affect the basic and novel characteristics of the claimed invention All compounds, compositions, formulations and compositions described herein that embody the invention are limited to the above. The articles and methods may, in alternative embodiments, be modified using the transition phrases "comprising," "essentially comprising," " "consisting essentially of" and "consisting of" The term "comprising" (and "including") may be more specifically defined by "comprise" or "comprises" or "having" or "including Related terms such as "including" and "constitute" a recited feature, for example. f) any composition, method, or process that "consists essentially of" or The present invention includes embodiments such as an embodiment of a process.
Claims
1. 1. A ceramic article comprising: (a) an alumina particle comprising a plurality of first alumina particles and a plurality of second alumina particles; a hard formation, wherein both of the plurality of particles are randomly distributed throughout the hard formation; Distributed in 1) The second alumina particles are 5 atomic percent or less of ZnI 2 Dye penetration test value The first alumina particles have ZnI of the second alumina particles. 2 Dye penetration test value At least twice as much ZnI 2 Dye penetration test value, 2) the hard formation has a total cross-sectional area, and each of the plurality of particles has a portion of the total cross-sectional area. and the cross-sectional area of the second alumina particles is 5% to 50% of the total cross-sectional area. A formation; (b) a catalytically active metal dispersed on the first and second alumina particles. Ramic items.
2. ZnI of the first alumina 2 The dye penetration test value of the second alumina is 2 dyed 10. The article of claim 1, having a material penetration test value at least three times greater.
3. ZnI of the first alumina 2 The dye penetration test value of the second alumina is 2 dyed 10. The article of claim 1, having a material penetration test value at least four times greater.
4. ZnI of the first alumina 2 Dye penetration test value is greater than 10 atomic percent The article of claim 1.
5. ZnI of the first alumina 2 Dye penetration test value is greater than 15 atomic percent The article of claim 1.
6. 2. The method of claim 1, wherein the second alumina has a dye penetrant test value of 3 atomic percent or less. The item described.
7. the ratio of the dye penetration test value of the first alumina to the dye penetration test value of the second alumina; The article of claim 1 , wherein the ratio of α, β ...
8. 2. The method of claim 1, wherein the cross-sectional area of the second alumina particles is between 8% and 40% of the total cross-sectional area. The article described in
9. The cross-sectional area of the second alumina particles is between 10% and 30% of the total cross-sectional area.
2. The article described in 1.
10. Approximately 0.2 cm 3 / g ~ approx. 0.6cm 3 The method of claim 1 further comprising a total pore volume of 1 g / g. Goods.
11. The total pore volume is about 0.3 cm 3 / g ~ approx. 0.5cm 3 / g according to claim 10. The item described.
12. The total pore volume is about 0.35 cm 3 / g ~ approx. 0.5cm 3 / g. The article described in
13. The catalytically active metal is selected from the group consisting of silver, platinum, palladium, nickel, and copper. The article of claim 1 .
14. A ceramic ceramic material comprising a hard matrix of alumina particles and a catalytically active metal in contact with said particles.
1. A process for the manufacture of a ceramic article, said process comprising: (a) a known weight and a d of about 0.2 to 100 microns 50 A plurality of first particles having a particle size Providing alpha alumina particles; (b) a material having a known weight and selected from the group consisting of fused alumina and platelet alumina; providing a plurality of second alpha alumina particles, the second alumina particles having an average particle size of about d from 5 to 400 microns 50 The first alumina particles have a particle size of d 50 Particle size and 2 alumina particles d 50 The ratio of the particle size to the particle size is 1:4 to 1:40, and the first alumina and a ratio of the weight of said first alumina to the weight of said second alumina is from 1:1 to 15:
1. 、 (c) mixing the plurality of alumina particles, thereby forming a mixture. mixing, wherein the particles are randomly distributed throughout the mixture; (d) forming the mixture into a plurality of malleable articles; (e) heating said malleable article to a sintering temperature of said alumina particles, thereby forming each malleable article. forming a malleable article from a hard formation of alumina particles, said particles in each of the plurality of particles being heating, wherein the atoms are randomly distributed throughout the hard formation; and depositing a catalytically active metal on said first and second alumina particles. Process.
15. The ratio of the weight of the first alumina to the weight of the second alumina is 1:1 to 10:
1.
15. The process of claim 14, wherein
16. The ratio of the weight of the first alumina to the weight of the second alumina is 1:1 to 5:
1.
15. The process of claim 14 .
17. d of the first alumina particles 50 Particle size and d of the second alumina particles 50 Ratio to particle size The process according to claim 14, wherein the ratio of the β-aminobutyric acid to the β-aminobutyric acid is from 1:5 to 1:
20.
18. d of the first alumina particles 50 Particle size and d of the second alumina particles 50 Ratio to particle size The process according to claim 14, wherein the ratio of the β-amino acid to the β-amino acid is from 1:8 to 1:
15.
19. The second alumina particles have a d 50 The particle size of claim 15. The process according to claim 14.
20. The second alumina particles have a d 50 The particle size of claim 15. The process according to claim 14.
21. The plurality of first alumina particles are 1.0 m 2 / g to 20.0 m 2 / g surface area The process of claim 14 .
22. The plurality of first alumina particles are 1.0 m 2 / g to 5.0 m 2 / g surface area The process of claim 14 .
23. The plurality of first alumina particles are 1.0 m 2 / g to 2.0 m 2 / g surface area The process of claim 14 .
24. The plurality of second alumina particles are 2 / g to 2.00 m 2 / g surface area 15. The process of claim 14, comprising:
25. The plurality of second alumina particles are 0.10 m 2 / g to 0.50 m 2 / g surface area 15. The process of claim 14, comprising:
26. The plurality of second alumina particles are 0.14 m 2 / g to 0.30 m 2 / g surface area 15. The process of claim 14, comprising:
27. 15. The process of claim 14, wherein the second alumina particles consist essentially of fused alumina. Process.
28. 15. The process of claim 14, wherein the second alumina particles comprise fused alumina.
29. The process of claim 14, wherein the second alumina particles consist essentially of platelet alumina. Seth.
30. 15. The process of claim 14, wherein the second alumina particles comprise platelet alumina.
31. The second alumina particles consist essentially of platelet alumina and fused alumina. Item 15. The process of item 14.
32. 15. The method of claim 14, wherein the second alumina particles are made of platelet alumina and fused alumina. The process described.
Citation Information
Patent Citations
New-type battery
JP1986171071A
Manufacture of porous alumina sintered body
JP1987252381A
Heat resistant and corrosion resistant adsorbent for iodine
JP1988162040A
Production of alumina porous carrier
JP1999043380A
Catalyst carrier
JP2004160459A